Microband sensor for As(III) analysis: Reduced matrix interference - Dudeney, Richard; Newman, Jeffrey; Davis, Frank; Setford, Steven; Tothill, Ibtisam E. (Wiley, 2017)
A portable sensor based on a microband design for arsenic detection in drinking water is presented. The work was focused to minimize interference encountered with a standard screen-printed electrodes featuring an onboard gold working electrode, carbon counter and silver−silver chloride pseudo-reference electrodes as composite coatings on plastic surface. The interference effect was identified as chloride ions interacting with the silver surface of the reference electrode and formation of soluble silver chloride complexes such as AgCl43−. By modification of the reference electrodes with Nafion membrane (5 % in alcohols), the interference was entirely eliminated. However, membrane coverage and uniformity can impact the electrodes reproducibility and performance. Hence, the sensor design was further considered and a microband format was produced lending favorable diffusive to capacitive current characteristics. Using the microband electrodes allowed As(III) detection with limit of detection of 0.8 ppb (in 4 M HCl electrolyte), inherently avoiding the problems of electrode fouling and maximizing analyte signal in river water samples. This is below the World Health Organization limit of 10 μg L−1 (ppb). The electrolyte system was chosen so as to avoid problems from other common metal ions, most notably Cu(II). The presented electrode system is cost effective and offers a viable alternative to the colorimetric test kits presently employed for arsenic analysis in drinking water.
Keywords: Microband electrode; Gold electrodes; Absorptive stripping voltammetry; Arsenic